Metapeachia schlenzae sp. nov. (Cnidaria: Actiniaria: Haloclavidae) a new burrowing sea anemone from Brazil, with a discussion of the genus Metapeachia - Gusmão, Luciana C. (Zootaxa, 2016)
The diversity of burrowing sea anemones from Brazil is poorly known with only three species recorded. Metapeachia schlenzae sp. nov. is described from specimens collected in the intertidal zone of São Sebastião and Cabo Frio in the southeastern coast of Brazil. Metapeachia schlenzae sp. nov. is the second species described for the genus and the second haloclavid recorded from Brazil. A comparison between Metapeachia schlenzae sp. nov. and Metapeachia tropica, the type species of the genus, is included. The two valid species of Metapeachia differ in the morphology of the conchula, internal anatomy, cnidae and geographical distribution.